Gut Microbiome in Inflammatory Bowel Disease: Role in Pathogenesis, Dietary Modulation, and Colitis-Associated Colon Cancer - John Gubatan; Theresa Louise Boye; Michelle Temby; Raoul S. Sojwal; Derek R. Holman; Sidhartha R. Sinha; Stephan R. Rogalla; Ole Haagen Nielsen (Microorganisms, 2022)
The gut microbiome has increasingly been recognized as a critical and central factor in inflammatory bowel disease (IBD). Here, we review specific microorganisms that have been suggested to play a role in the pathogenesis of IBD and the current state of fecal microbial transplants as a therapeutic strategy in IBD. We discuss specific nutritional and dietary interventions in IBD and their effects on gut microbiota composition. Finally, we examine the role and mechanisms of the gut microbiome in mediating colitis-associated colon cancer.